Loyalty towards City as Tourism Destination: The Role of Destination Image and Destination Quality - Raden Mochamad Rafly Hilmiawan,Mohamad Reza Pahlevi,Rana Maulana Pribadi,Lusianus Kusdibyo,Virgiawan (International Conference on Industrial Revolution for Polytechnic Education, 2020)
Tourist destinations in a city can certainly be a special attraction for tourists to visit the city. City Tourism has created a lot of profitable business activities, both for the government and the local community. However, if the number of tourist visits experienced a fluctuation, it will certainly disrupt the benefits of both parties. Meanwhile, the image and destination quality are important factors that have been widely studied in influencing tourist satisfaction and loyalty. This study examines the relationship between these factors. The questionnaires were distributed to tourists who have visited Bandung using a five-point Likert scale. Of the 430 questionnaires collected, 384 questionnaires were appropriate for further analysis. This study uses partial least squares structural equation modeling (PLS-SEM) analysis to examine the interrelationship between factors. The results show that destination image variables have a significant direct influence on tourist satisfaction and loyalty. In addition, destination quality variables significantly affect tourist satisfaction. However, the destination quality variable does not have a direct influence on tourist loyalty. On the other hand. the tourist satisfaction variable has a direct influence on tourist loyalty. Finally, the relationship of each variable in this study can provide a new understanding for tourism service providers in improving city tourism attractions.